Skill differentiation in soccer ball juggling on an unstable surface - Kizuka, T.; Itaya, A.; Iwami, M.; Iijima, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
Even persons who are skilled at soccer ball juggling experience a decrease of performance when juggling on an unstable surface. We examined this activity in 19 college soccer players to determine the variation in the degree of skill deterioration. To investigate the associated factors, we measured posture retention, head sway, and muscle activity while juggling on a stable and an unstable surface. We measured the number of ball contacts while subjects juggled soccer balls for 20 s on both surfaces. We then divided the subjects into two groups: a skilled group, comprising 9 subjects whose average number of ball contacts fell from 57.6 to 55.2 when changing from the stable to the unstable surface, respectively; and a semi-skilled group, comprising 10 subjects whose average number of ball contacts fell from 55.8 to 32.5. On the unstable surface, the semi-skilled group spent significantly less time standing on one leg with eyes closed (11.4 vs. 23.7 s), showed a significantly higher maximal left-to-right head sway (41.5 vs. 30.4 cm), and had significantly higher activity in the biceps femoris (52.5 vs. 26.0%RMS). On the stable surface, the semi-skilled group showed a significantly higher maximal left-to-right head sway (25.3 vs. 17.2 cm) and had significantly higher activity in the biceps femoris (31.7 vs. 19.3%RMS). In addition, the reduction in the number of ball contacts on the unstable surface was correlated with increased biceps femoris activity (r=-.677). Overall, soccer ball juggling control in the semi-skilled group was slightly inferior to that in the skilled group. The present results show that the differences are small enough to negate the number of ball contacts during soccer ball juggling on a stable surface as an effective measure. When instability created a disturbance, juggling performance in the semi-skilled group declined due to excessive muscle activity of the biceps femoris, which led to unnecessary freezing of the knee and hip joints and increased head sway. The skilled group was able to better suppress the increase in control load caused by the instability, so that interference in juggling performance was lower. Manifesting a skill difference that cannot be determined only by the number of soccer ball juggling contacts on a stable surface may require an additional task involving posture control on an unstable surface.